EFEK BEHAVIOR-DRIVEN DEVELOPMENT, HEXAGONAL ARCHITECTURE DAN EVENT SOURCING TERHADAP PENGEMBANGAN PERANGKAT LUNAK BISNIS - Abdulah, Muhamad Biyan; Triayudi, Agung; ingsih, Andrian (Pelita Nusantara Medan, 2020)
Software usage in business world are growing. But as time passes, many problems occurs as both software users and software features that wished to be developed increases, such as performance problems and maintainibility problems. Theres some techniques that has been developed to solve these kinds of problem (such as MVC framework, Test-Driven Development, Domain-Driven Design) but sometimes these techniques criticized as adding more problems instead. In this journal we will present our findings from our research which utilizes two techniques that is Behavior-Driven Development and Event Sourcing and observes its effects in our?Assignment Management System? we?ve developed.